The Inhibitory Effect of Artesunate on Excessive Endoplasmic Reticulum Stress Alleviates Experimental Colitis in Mice - Yin, Shaojie; Li, Liuhui; Tao, Ya; Yu, Jie; Wei, Simin; Liu, Mingjiang; Li, Jingui (Frontiers in Pharmacology, 2021)
Endoplasmic reticulum (ER) stress may contribute to the pathogenesis and perpetuation of ulcerative colitis (UC). Previous studies have shown artesuante (ARS) has the protective effect on experimental UC. Therefore, it can be assumed that ARS can regulate ER stress and its related reactions. Dextran sulfate sodium (DSS) induced UC model in mice was used to testify this hypothesis. The results clearly showed that DSS exposure caused excessive ER stress evidenced by a markedly increase of GRP78 and CHOP expression, and then activated the ER stress sensors PERK, IRE1, ATF6 and their respective signaling pathways, followed by upregulated caspase12 and lowered Bcl-2/Bax ratio. However, ARS treatment significantly inhibited the occurrence of ER stress via preventing the activation of PERK-eIF2α-ATF4-CHOP and IRE1α-XBP1 signaling pathways, concurrently ER-stress-associated apoptosis in colon tissues. Moreover, ARS treatment remarkably inhibited the activation of NF-κB and the expression levels of pro-inflammatory cytokines, improved the clinical and histopathological alterations as well as maintained the expression of claudin-1 and Muc2 in mucosal layer of colon. Notably, the classic ER stress inhibitor 4-phenyhlbutyric acid enhanced the beneficial effects of ARS; in contrast, the ER stress inducer 2-deoxy-d-glucose substantially abrogated the above-mentioned effects, uncovering the involvement of ER stress in the response. These findings indicated the protection of ARS on UC is associated with its suppressing excessive ER stress mediated intestinal barrier damage and inflammatory response. This study provides a novel aspect to understand the mechanism of ARS against UC.